2020
DOI: 10.31234/osf.io/dsytn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Experience of Awe: Validating the Situational Awe Scale

Abstract: We introduce the Situational Awe Scale (SAS), a self-report measure to assess the momentary, phenomenological experience of awe. An exploratory factor analysis in Study 1 suggested a four-factor structure (connection, oppression, chills, and diminished self), and provided initial evidence of the measure’s convergent and criterion validity. Study 2 provided evidence for the structural validity of the SAS by confirming the factor structure uncovered in Study 1, and replicated the convergent and criterion validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 32 publications
(61 reference statements)
14
22
1
Order By: Relevance
“…The interaction, although it was marginally significant, indicated that positive awe and threatened awe have, at least, a different influence on the generosity at the least. Furthermore, the present result corresponds to the previous hypothesis that effects on connection would differ between the types of awe (e.g., eliciter, valence) (Van Cappellen and Saroglou, 2012;Krenzer, 2018), suggesting that positive awe may promote the generosity toward norm violation by emphasizing connection to others with various attributes, while threatened awe does not, because it does not emphasize connection. On the other hand, threatened awe often leads to the enhancement of connections between people and other-focused behavior and culture, alleviating feelings of loss in the face of threatened-awe inducing events (Nomura et al, in press).…”
Section: Difference Between the Two Types Of Awesupporting
confidence: 89%
See 3 more Smart Citations
“…The interaction, although it was marginally significant, indicated that positive awe and threatened awe have, at least, a different influence on the generosity at the least. Furthermore, the present result corresponds to the previous hypothesis that effects on connection would differ between the types of awe (e.g., eliciter, valence) (Van Cappellen and Saroglou, 2012;Krenzer, 2018), suggesting that positive awe may promote the generosity toward norm violation by emphasizing connection to others with various attributes, while threatened awe does not, because it does not emphasize connection. On the other hand, threatened awe often leads to the enhancement of connections between people and other-focused behavior and culture, alleviating feelings of loss in the face of threatened-awe inducing events (Nomura et al, in press).…”
Section: Difference Between the Two Types Of Awesupporting
confidence: 89%
“…While positive awe strengthens a sense of being connected to everything, threatened awe does not (Krenzer, 2018). If positive awe enhances a sense of connection to other people and even deviators, independently of social hierarchy, it is postulated that threatened awe promotes neither a tolerant attitude nor an intolerant attitude toward others' norm violations; as suggested by previous research, threatened awe may enhance strict attitudes toward norm violations (Gelfand et al, 2011;Gelfand and Lun, 2013;Kastenmüller et al, 2013;Mrazek et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our own research, we have taken theoretically derived conceptualizations of awe as a basis for developing a self-report measure of transient or situational awe (Situational Awe Scale (SAS); [7]). Hundreds of individuals, participating via online surveys or in the lab, have told us about their experiences with awe.…”
Section: Museums and Awementioning
confidence: 99%